2017
DOI: 10.1002/jbm.b.34012
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical interactions between pancreatic cancer cells and pristine carbon nanotube substrates: Potential application for pancreatic cancer tissue engineering

Abstract: Novel synthetic biomaterials able to support direct tissue growth and retain cellular phenotypical properties are promising building blocks for the development of tissue engineering platforms for accurate and fast therapy screening for cancer. The aim of this study is to validate an aligned, pristine multi-walled carbon nanotube (CNT) platform for in vitro studies of pancreatic cancer as a systematic understanding of interactions between cells and these CNT substrates is lacking. Our results demonstrate that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…72 In terms of morphological characteristics within the 3D scaffold, as veried by SEM imaging, the AsPC-1 cells retained their foci-like epithelial shape (Fig. 3a), 79,80 while PANC-1 cells had an elongated epithelial morphology (Fig. 3b).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…72 In terms of morphological characteristics within the 3D scaffold, as veried by SEM imaging, the AsPC-1 cells retained their foci-like epithelial shape (Fig. 3a), 79,80 while PANC-1 cells had an elongated epithelial morphology (Fig. 3b).…”
Section: Discussionmentioning
confidence: 92%
“…We have previously reported this formation of PANC-1 cellular masses in carbon nanotube based lms. 80 FN is considered to interact with the cell surface integrin receptors, which may result in enhancing the cell-cell interactions and consequently leading to cell clustering. 75,91 This evidence is further supported by the group of Da Rocha-Azevedo et al, who showed that the cell contraction in clustering requires the presence of FN.…”
Section: Discussionmentioning
confidence: 99%
“…2 More recently, 3D in vitro models have emerged and are being developed as low cost, promising alternatives to animals. 7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] However, most studies focus on the development of the actual 3D model and, to the best of our knowledge, there are very limited 3D studies on PDAC treatment screening (chemotherapy and radiotherapy) with most studies conducted in 3D spheroids (cell aggregates). 14,32,[34][35][36][49][50][51][52] Generally, these studies report a higher resistance of PDAC to treatment in 3D when compared to 2D cultures, a trend which is in closer alignment with in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cell differentiation was also enhanced when the growth took place on DWCNT [37]. Raw (non-functionalised) aligned MWCNT successfully sustained the growth and proliferation of pancreatic cancer cells, exhibiting a new approach for the study of this kind of cancer [38].…”
Section: Carbon Nanotubes (Cnt) For Biomedical Applicationsmentioning
confidence: 99%